Fungus-mediated biosynthesis of silica and titania particles - Bansal, Vipul; Rautaray, D.; Bharde, Atul A.; Ahire, Kedar C.; Sanyal, A.; Ahmad, Absar; Sastry, Murali (Journal of Materials Chemistry, 2005)
The synthesis of inorganic materials by biological systems is characterized by processes that occur at close to ambient temperatures, pressures and neutral pH. This is exemplified by biosilicification in marine organisms such as diatoms while laboratory-based synthesis of silica involves extreme temperature and pH conditions. We show here that silica and titania particles may be produced by challenging the fungus Fusarium oxysporum with aqueous anionic complexes SiF62- and TiF62- respectively. Extra-cellular protein-mediated hydrolysis of the anionic complexes results in the facile room temperature synthesis of crystalline titania particles while calcination at 300 degrees C is required for crystallization of silica.

Development and application of a method for analysis of lufenuron in wheat flour by gas chromatography-mass spectrometry and confirmation of bio-efficacy against Tribolium castaneum (Herbst) (Coleoptera : Tenebrionidae) - Ahire, Kedar C.; Arora, Manjit S.; Mukherjee, Samindra N. (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2008)
A new analytical method using gas chromatography with mass spectrometry (GC-MS) for the quantitative determination of lufenuron, a benzoylphenylurea (BPU) class of insecticide, from wheat flour has been developed and applied for time-dependant residue monitoring in treated wheat flour. The analyte was extracted from wheat flour by a single step solid-liquid extraction by using ethyl acetate and subsequently cleaned up using the Primary Secondary Amine as a sorbent prior to GC-MS analysis. The present method provides sufficient sensitivity as reflected by the values of limit of detection (LOD) and limit of quantification (LOQ), 5 ng/mL (S/N similar to 3) and 50 ng/mL (the lowest validation point on the calibration curve), respectively. The calibration curve showed an excellent linearity in the concentration range of 50-1000 ng/mL (r(2) = 0.998). The average recovery for spiked samples at three concentrations (150, 300, and 450 ng/g) was 98.23 +/- 2.52% R.S.D. The method was applied for the determination of lufenuron residues in treated wheat flour samples. Simultaneous determination of bio-efficacy of lufenuron residues was also carried out against the red flour beetle, Tribolium castaneum to correlate the actual residual effect of lufenuron as detected by the analytical method, over a period of 3 months. The findings revealed that the residual concentration of lufenuron were neither uniform nor in descending order over a period of 3 months in wheat flour, possibly because of an uneven dispersal in the treated wheat which was subsequently milled into flour, as confirmed by GC-MS analysis. However, the residues of lufenuron were sufficient to produce 100% mortality of T. castaneum larvae up to 3 months. The results have been discussed in view of the potential of lufenuron as a candidate molecule for the control of stored product pests. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: bio-efficacy; GC-MS; lufenuron; method development; residue analysis; Tribolium castaneum; Wheat